Functional abilities in children and adults with the CDKL5 disorder - Fehr, S.; Downs, Jennepher; Ho, G.; de Klerk, N.; Forbes, D.; Christodoulou, J.; Williams, S.; Leonard, H. (John Wiley & Sons, Inc., 2016)
Functional abilities in the CDKL5 disorder have been described as severely impaired, yet some individuals are able to run and use phrases for speech. Our study investigated gross motor, hand function, and expressive communication abilities in individuals with the CDKL5 disorder. Data for 108 females and 16 males registered with the International CDKL5 disorder database and with a pathogenic CDKL5 mutation were analyzed. Relationships between functional abilities, age, genotype, and gender were analyzed using regression models. Over half of the females could sit on the floor and nearly a quarter could walk 10 steps. Fewer males could complete these tasks although one boy was able to sit, walk, and run. Most females and few males were able to pick up a large object. Females mostly used gestures to communicate while males mostly used other forms of non-verbal communication. Compared to those with no functional CDKL5 protein, individuals with truncating variants after aa 781 were more likely to be able to stand (OR 5.7, 95%CI 1.2, 26.6) or walk independently (4.3, 95%CI 0.9, 20.5), and use more advanced communication methods such as words (OR 6.1, 95%CI 1.5–24.2). Although abilities were markedly impaired for the majority with the CDKL5 disorder, some females and a few males had better functional abilities. This variability may be related to underlying gene variants, with females with a late truncating variant having better levels of ability than those with no functional protein.